Acute acrylonitrile exposure inhibits endogenous H2S biosynthesis in rat brain and liver: The role of CBS/3-MPST-H2S pathway in its astrocytic toxicity. (15th March 2021) - Yang, Bobo; Zhao, Wenjun; Yin, Changsheng; Bai, Yu; Wang, Suhua; Xing, Guangwei; Li, Fang; Bian, Jinsong; Aschner, Michael; Cai, Jiyang; Shi, Haifeng; Lu, Rongzhu
Abstract: Hydrogen sulfide (H2 S) as the third gasotransmitter molecule serves various biological regulatory roles in health and disease. Acrylonitrile (AN) is a common occupational toxicant and environmental pollutant, causing brain and liver damage in mammals. The biotransformation of AN is dependent-upon reduced glutathione (GSH), cysteine and other sulfur-containing compounds. However, the effects of AN on the endogenous H2 S biosynthesis pathway have yet to be determined. Herein, we demonstrated that a single exposure to AN (at 25, 50, or 75 mg/kg for 1, 6 or 24 h) decreased the endogenous H2 S content and H2 S-producing capacity in a dose-dependent manner, both in the cerebral cortex and liver of rats in vivo . In addition, the inhibitory effects of AN (1, 2.5, 5, 10 mM for 12 h) on the H2 S content and/or the expression of H2 S-producing enzymes were also found both in primary rat astrocytes and rat liver cell line (BRL cells). Impairment in the H2 S biosynthesis pathway was also assessed in primary rat astrocytes treated with AN. It was found that inhibition of the cystathionine-β-synthase (CBS)/3-mercaptopyruvate sulfurtransferase (3-MPST)-H2 S pathway with the CBS inhibitor or 3-MPST-targeted siRNA significantly increased the AN-induced (5 mM for 12 h) cytotoxicity in astrocytes. In turn, CBS activation or 3-MPST overexpression as well as exogenous NaHS supplementation significantly attenuated AN-induced cytotoxicity. Taken together, endogenous H2 S biosynthesis pathway was disrupted in rats acutely exposed to AN, which contributes to acute AN neurotoxicity in primary rat astrocytes.